ENT 530 Social Media Portfolio: Miniechicken / Alia Yasmin Anuar - Anuar, Alia Yasmin (2021)
This report is about a social media portfolio for a simulated business under course of Principles of Entrepreneurship (ENT530) which is a course under the Faculty of Business Administration and Management. The business name is The Miniechicken owned by Alia Yasmin binti Anuar. A business named The Miniechicken owned by Alia Yasmin binti Anuar is a food business. This business sells Korean chicken with their special recipe of sauce that can make people want more of Miniechicken. The sauce is hot and spicy and it is homemade by using our secret recipe which make it more special and unique. In this report, it contains the information of the business such as the mission and vision of the company, what is the main product or services provided by this business, the prices and many more which explain more about this business Other than that, this report includes the creation of a Facebook page for this business with over 100 likes. It will include all those posting regarding the business that we made in our Facebook page name The Miniechicken. The postings include the teasers of the product, the soft sells and also the hard sells in order to attract customers. The theme color for our Facebook page are black, red and white to describe the spiciness of The Miniechicken